Training on climate-smart forage and feed innovations - Tanzania - Mpelangwa, Eziacka; Kimaro, Anthony; Gosling, Amanda; Cramer, Laura K. (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
To address land degradation, climate change, and livestock feed gaps in semi-arid Tanzania the Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) project, in partnership with the Center for International Forestry Research and World Agroforestry (CIFOR-ICRAF), initiated the spillover of validated climate-smart feed and forage technologies, with a focus on Gliricidia sepium agroforestry practices. On the 5th of December 2024, a workshop was held in Dodoma, Tanzania, to improve training participants’ knowledge on the selected technologies as well as enhance partnerships and collaboration to accelerate the spillover process. This workshop report highlights the need for the training and provides information on the participants and how the workshop was planned and conducted. The report concludes with the key challenges raised and proposed actions for the way forward.